Role of Social Media Sites in Improving and Developing the Educational Process in Secondary Schools in Jordan - Bani Irshaid, Muhammad Noor (Technium Social Sciences Journal, 2020)
This study aims to learn about the role of social media sites in improving and developing the educational process in secondary schools in Jordan, the descriptive analytical method was used to suit the nature of the study, and the questionnaire was used as a tool for study, and the sample of the study consisted of (50) of teachers working in secondary schools in Jordan. The results of the study found that high degree and statistical significance for the role of social networking sites in developing and improving the educational process in secondary schools. The study recommends that Holding seminars and meetings to publicize the importance of social networking sites in the educational process, and ways to use them safely and correctly, and Provide training courses for teachers to inform them of how to use social media sites and their tools and applications in the educational process.